Workshop Virtual: Peningkatan Keterampilan Penggunaan Mendeley dan Pemanfaatan Sumber Pustaka Melalui Layanan Penguasaan Konten - Oktasari, Maria; Solihatun, Solihatun; Syahputra, Yuda (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The preparation of final assignments/scientific articles carried out by students is often faced with various problems. One of them is the difficulty in finding a reference source / reference for making a final project/ scientific article and the limited skills of students in using citation and reference software: mendeley. This community service aims to improve skills in using mendeley and utilizing library sources for students. Participants consisted of 186 people from 23 university in Indonesia, who were obtained through random samplingThe data was collected online using 10 questions related to the skill of using Mendeley with the Guttman Scale model (multiple choice). Data were analyzed using nonparametric statistical techniques using the Wilcoxon Signed Ranks Test. The findings show that content mastery services with virtual workshops are effective in improving mendeley skills and utilization of student library resources.